THE PROCESS OF GLOBALIZATION BEFORE AND AFTER THE 2008 FINANCIAL CRISIS - Aničić, Jugoslav; Simić, Nataša; Petrović, Vesna; Aničić, Dušan (Journal of process management and new technologies, 2020)
Big financial crisis from 2008 has dramatically changed globalization process by reducing cross-border flow of capital, to a large degree. Crisis has shown numerous deficiencies and negative sides of this process, and there was a big displacement of world economy from developed western countries towards China and other countries in accelerated development. Symptoms of de-globalization, such as populism, economic protectionism and similar, haven’t significantly changed the picture of constant integrative processes worldwide. Undoubtedly, in future, globalization will mostly be dependent on the three biggest and most significant economic, political and social entities in the world – USA, EU and China. Tail wind to an overall globalization process is given by Globalization 4.0, which is based on automatization by digital technologies with use in not only production processes, but in health care, education, transport, supply industry as well.
Keywords: globalization; international relations; USA; EU; China